2017
DOI: 10.1002/ange.201706647
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Identification of an Atomic Oxygen Structure on Catalytic Gold Nanoparticles

Abstract: Interactions between oxygen and gold surfaces are fundamentally important in diverse areas of science and technology.I nt his work, an oxygen dimer structure was observed and identified on gold nanoparticles in catalytic decomposition of hydrogen peroxidetooxygen and water.This structure,which is different from isolated atomic or molecular oxygen surface structures,w as observed with in situ surfaceenhanced Raman spectroscopic measurements and identified with density functional theory calculations.T he experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The remaining two bottom layers were constrained at the bulk Ni positions, accounting for the bulk structure. Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces [14–23] …”
Section: Methodsmentioning
confidence: 99%
“…The remaining two bottom layers were constrained at the bulk Ni positions, accounting for the bulk structure. Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces [14–23] …”
Section: Methodsmentioning
confidence: 99%
“…As an example, our study with monodisperse 5, 50 and 400 nm Au particles showed that the rate of catalytic H 2 O 2 decomposition increased dramatically with decreasing Au particle size when the total number of surface Au atoms was kept constant. 7,8 For adsorbates, experimental and computational studies demonstrate that adsorption energies and, consequently, geometries and vibrational frequencies of atomic and molecular oxygen on Au surfaces are highly dependent on the size of Au particles. [7][8][9] As an example, while molecular oxygen on Au(111) is unstable, its adsorption becomes progressively more energetically favorable with decreasing Au particle size.…”
mentioning
confidence: 99%
“…7,8 For adsorbates, experimental and computational studies demonstrate that adsorption energies and, consequently, geometries and vibrational frequencies of atomic and molecular oxygen on Au surfaces are highly dependent on the size of Au particles. [7][8][9] As an example, while molecular oxygen on Au(111) is unstable, its adsorption becomes progressively more energetically favorable with decreasing Au particle size. The O-O bond distance gradually increases, and its stretching vibration, n(O-O), accordingly, progressively decreases from 1185 cm À1 for a bulk Au surface to 1049 cm À1 for a subnanometer-size Au cluster.…”
mentioning
confidence: 99%
See 2 more Smart Citations